2020
DOI: 10.3390/ijms21020675
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cavernous Malformation Proteins in Barrier Maintenance and Regulation

Abstract: Cerebral cavernous malformation (CCM) is a disease characterized by mulberry shaped clusters of dilated microvessels, primarily in the central nervous system. Such lesions can cause seizures, headaches, and stroke from brain bleeding. Loss-of-function germline and somatic mutations of a group of genes, called CCM genes, have been attributed to disease pathogenesis. In this review, we discuss the impact of CCM gene encoded proteins on cellular signaling, barrier function of endothelium and epithelium, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 156 publications
0
20
0
Order By: Relevance
“…avernous angiomas (CAs) are characterized by dysmorphic dilated vascular capillaries, or caverns, lined by endothelium [1][2][3] . About 30-40% of CA patients have autosomal dominant inherited germline mutations in one of three known CA genes (CCM1/KRIT1, CCM2/Malcavernin, and CCM3/PDCD10), and develop multifocal lesions throughout the brain and spinal cord.…”
mentioning
confidence: 99%
“…avernous angiomas (CAs) are characterized by dysmorphic dilated vascular capillaries, or caverns, lined by endothelium [1][2][3] . About 30-40% of CA patients have autosomal dominant inherited germline mutations in one of three known CA genes (CCM1/KRIT1, CCM2/Malcavernin, and CCM3/PDCD10), and develop multifocal lesions throughout the brain and spinal cord.…”
mentioning
confidence: 99%
“…The pleiotropic functions of KRIT1 have been clearly implicated in the maintenance of endothelial cell homeostasis and blood-brain barrier integrity through the control of coordinated molecular and cellular responses to oxidative stress and inflammation, which in turn suggest novel mechanisms of CCM disease onset and severity, providing new preventive and therapeutic perspectives ( Antognelli et al, 2020 ; Choquet et al, 2016 ; De Luca et al, 2018 ; Finetti et al, 2020 ; Gibson et al, 2015 ; Goitre et al, 2017 ; Kim et al, 2020 ; Marchi et al, 2016 ; Perrelli et al, 2018 ; Retta and Glading, 2016 ; Trapani and Retta, 2015 ). On the other hand, recent evidence demonstrates that the consequences of KRIT1 loss-of-function mutations extend beyond the pathogenesis of CCM disease, being also implicated in the development of aortic endothelial dysfunction and atherosclerosis ( Vieceli Dalla Sega et al, 2019 ), as well as of epithelial barrier dysfunction in the gastrointestinal tract ( Wei et al, 2020 ). Consistent with its emerging functions in distinct tissues, KRIT1 has been shown to be expressed almost ubiquitously.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade there has been significant progress in understanding KRIT1 functions, providing useful insights into molecular mechanisms of CCM disease pathogenesis. Loss of KRIT1 has been shown to affect major cell structures and signaling mechanisms involved in the formation and stability of cell–cell and cell‒matrix junctions and the maintenance of endothelial and epithelial barriers, including the blood-brain barrier ( Glading et al, 2007 ; Liu et al, 2013 ; Maddaluno et al, 2013 ; Stockton et al, 2010 ; Wei et al, 2020 ; Zawistowski et al, 2002 ; Zhang et al, 2001 ). Furthermore, accumulated evidence has clearly shown that the effects of KRIT1 loss-of-function on the stability of endothelial and epithelial barriers are due to an alteration of the complex machinery governing redox homeostasis and the cellular responses to oxidative stress and inflammation ( Antognelli et al, 2018a , b ; Choquet et al, 2016 ; Cianfruglia et al, 2019 ; Corr et al, 2012 ; Finetti et al, 2020 ; Gibson et al, 2015 ; Goitre et al, 2010 , 2014 , 2017 ; Marchi et al, 2015 ; Retta and Glading, 2016 ; Tang et al, 2017 ; Retta et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Focal BBB breakdown takes center stage in CCMs lesion development. Some of the underlying mechanisms involved include abnormal angiogenesis, disorganization of the endothelial TJ complex, alterations in the signaling pathways that regulate these processes, alteration in anti-coagulation vascular domain and inflammation [ 191 ].…”
Section: Modeling the Bbb Pathology Of Cerebrovascular Diseasementioning
confidence: 99%